O Infinito segundo Giordano Bruno - Antonio Abdalla Baracat Filho (2009)
The dissertation investigates the infinite, as conceived by Giordano Bruno. The infinite was object of studies in the Classical Antiquity, so much on the part of the atomism as of the aristotelianism. However, Giordano Bruno went the first philosopher to defend the your existence in act, in the sensitive and supersensitive dimensions, for beyond of the space and of the time, both in the cosmological as in the anthropological range, in confrontation with aristotelian thought, which only admitted the infinite in potency. The hypothesis that guides the research is that the nolan doctrine of the infinite remains valid, since it rids the universe of chains of finitists dogmas, spiritualists and materialists, paving the way for the advancement of ethics, aesthetics, epistemology and other areas of knowledge, with invaluable impact on individual and social life of men.